(untitled) (Veterinary Science, 2017)
The intensity of the immune response is regulated by amino acid motifs in antigen recognition sites (ARS) present in the pockets of Major Histocompatibility Complex molecules. The objective of this work was to study the association between these motifs and resistance/ susceptibility to mastitis measured by somatic cell counts (SCC) in milk from Holstein cattle from the province of La Pampa. The population was divided into: 1) case group with high SCC and presence of mastitis (≥ 250,000 cells/ml susceptibility) and 2) control group under SCC (< 250,000 cells/ml resistant). From a sample of 128 animals, 40 were genotyped for the second exon of BoLA-BRB3 gene by direct sequencing technique, 20 cows for each group. A total of 24 alleles were detected in the analyzed population. Gene frequencies of amino acid motifs of the five pockets (1, 4, 6, 7 and 9) from ARS in the two groups of animals were calculated. Test Odds Ratio (OR) Woolf-Haldane was used to study the association. No significant differences between amino acid motifs of pockets 1, 4, 7 and 9 between groups with high and low SCC were found. However, the T 11 Y 30 motif in pocket 6 (found in BoLA-DRB3 * 0601, * 0901 and * 4401 alleles) showed a significant OR value = 0.11 (p = 0.03). This suggests an association between this motif with a lower risk of developing mastitis. The role of amino acid motif T 11Y 30 in animal immune response should be validated in independent populations